EFFECT OF CONSUMING TOMATO (LYCOPERSIUM COMMUNE) JUICE IN LOWERING BLOOD PRESSURE IN PREGNANT MOTHERS WITH HYPERTENSION - Theresia Anita; Agus Suwandono; Ida Ariyanti; Noor Pramono; Suryati Kumorowulan (Belitung Raya Foundation, Indonesia, 2017)
Background: High blood pressure during pregnancy can pose significant problems such as preeclampsia, eclampsia, and premature birth. Thus, early prevention is needed. Consuming tomato (lycopersium commune) juice is considered effective to reduce blood pressure in pregnant women. Objective: This study aims to examine the effect of tomato juice on the decrease in blood pressure of pregnant women with hypertension in pregnancy. Methods: This study was a quasi-experiment with pretest-posttest control group. This research was conducted at the working area of the Community Health Center of Magelang Indonesia in July 2016 - January 2017. The target population of this study was pregnant women in trimester I, II, and III with high blood pressure. There were 30 samples selected using consecutive sampling, with 15 assigned in the experiment and control group. Wilcoxon test was performed for data analysis. Results: There was a statistically significant difference in systolic and diastolic blood pressure before and after given tomato juice with p = 0.001 (<0.05). Conclusion: Consuming tomato juice can be one of the efforts to reduce blood pressure in pregnant women with hypertension.